ANALISIS KEPUASAN KERJA KARYAWAN DITINJAU DARI PENGEMBANGAN KARIR, FASILITAS KERJA DAN LINGKUNGAN KERJA - Aryanto, Tossy; Junaidi, Achmad; Wahyudi, Wahyudi; Febrianti, Sania (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The purpose of this study was to analyze the influence of career development, work facilities and work environment on employee job satisfaction in the technical building of PT Selalu Cinta Indonesia in Salatiga. This type of research is quantitative research. The sampling technique used random sampling technique. Data collection using questionnaires. The sample taken was 100 employees who work in the technical building of PT Selalu Cinta Indonesia in Salatiga. The independent variables in this study are career development (X1), work facilities (X2), and work environment (X3) while the dependent variable is employee job satisfaction (Y). The results of the study showed that there was a positive and significant influence on job satisfaction, namely the work environment (X3) with a regression coefficient of 0.362; then the work facility variable (X2) with a regression coefficient of 0.347, and the career development variable (X1) with a regression coefficient of 0.244. The suggestion in this study is the importance of management to improve career development, work facilities and work environment for employee job satisfaction. Such as improving work facilities and work environment and conducting training for career development